Digital currencies in financial networks - Olli Castrén; Ilja Kristian Kavonius; Michela Rancan (European Banking Authority (EBA), 2020)
We introduce a digital currency, either as a central bank digital currency (CBDC) or a financial crypto asset (stablecoin), in the network of financial accounts. Simulating a shift of deposits by both households and non-financial corporations from the banking sector to the digital currency, we model the different responses of the affected institutional sectors. We find that the introduction of a digital currency generates significant adjustments in the balance sheets of all sectors, may trigger large moves in securities prices and induces changes in the network structure. The economic impacts vary depending on the design of the digital innovation, the size of the deposit shift, the channels through which the balance sheet adjustments take place and the timing of the initiative.
Keywords: G21; E58; 330; Digital Currency; Central Bank Digital Currency; Stablecoins; Macro-network; Financial Intermediation; Financial Stability